Peranan Guru dalam Pembelajaran Daring Pada Masa Pandemi Covid - 19 - Indah Winarsieh; Itsni Putri Rizqiyah (Indonesian Journal of Teacher Education, 2020)
Abstract Teachers are a key element that plays an important role in formal education. Its existence is a determinant of the success of students and the quality of education. During the covid-19 pandemic, teachers are required to be able to demonstrate the competence of teachers in guiding, training, educating, and teaching their students. In accordance with the policy set by the government, it is mandatory for all schools to conduct online learning systems, therefore teachers and students must work together in order for the purpose of learning during the COVID-19 pandemic to be achieved. Teachers must continue to perform their duties in teaching, training, encouraging creativity even without having to come face-to-face with students. in this case, it is necessary for teachers to support the learning process online (online). This article aims to describe the role of teachers in online learning during the COVID-19 pandemic. The method used in this study is the library study method. The results showed that teachers played an important role in the learning process, especially during the COVID-19 pandemic. Teachers need to be able to motivate students to stay passionate about learning. Keywords: Teacher Roles, Online Learning, COVID-19 Abstrak Guru merupakan elemen utama yang memiliki peran penting dalam pendidikan formal. Keberadaannya menjadi penentu keberhasilan peserta didik dan kualitas pendidikan. Pada masa pandemi Covid 19 saat ini guru dituntut harus mampu menunjukkan kompetensi guru dalam membimbing, melatih, mendidik, dan mengajar siswanya. Sesuai dengan kebijakan yang ditetapkan oleh pemerintah yaitu diwajibkan untuk seluruh sekolah melakukan sistem pembelajaran secara daring, oleh karenanya guru maupun siswa harus sama-sama bekerja sama agar tujuan dari pembelajaran selama pandemic COVID-19 tercapai. Guru harus tetap menjalankan tugasnya dalam mengajar, melatih, mendorong kreativitas meskipun tanpa harus bertatap muka secara langsung dengan siswa. dalam hal ini diperlukan peran guru dalam menunjang proses pembelajaran secara daring (dalam jaringan). Tulisan ini bertujuan untuk mendeskripsikan peranan guru dalam pembelajaran daring dimasa pandemi COVID-19. Metode yang digunakan dalam penelitian ini ialah metode studi pustaka. Hasil kajian menunjukkan bahwa guru memiliki peranan penting dalam proses pembelajaran khususnya pada masa pandemi COVID-19. Guru harus bisa memotivasi siswa agar tetap semangat dalam belajar. Kata Kunci: Peranan Guru, Pembelajaran Daring, COVID-19